Met and unmet care needs of older people with dementia living at home: Personal and informal carers' perspectives. (August 2019) - Mazurek, Justyna; Szcześniak, Dorota; Urbańska, Katarzyna; Dröes, Rose-Marie; Rymaszewska, Joanna
In Poland, there are few reports of the holistic approach to caring for older people with dementia. The aim of this study was to assess the needs of people with dementia living at home. This was done by evaluating the perspective of people with dementia themselves and that of their carers. The study included 47 people diagnosed with mild to moderate dementia and 41 informal carers, all living in Wroclaw in Poland, involved in the MeetingDem project. The needs were assessed using the CANE. Other scales used were: the MMSE, the GDS and the QOL-AD. The carers reported significantly more needs, both met and unmet, than the people with dementia themselves. The most frequent reported unmet needs both by the people with dementia and their carers included activities of daily living, psychological distress and the need for company. Based on this study's findings, tailored multidisciplinary treatment, adjusted to their needs and wishes, can be offered thus creating integrated and individualised support.